Specificità del Diritto amministrativo canonico e “amministrazione di missione”. La ministerialità ecclesiale come fattore riqualificativo per una autonomia ontologico-disciplinare (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Ministerialità e missionarietà del Diritto canonico - 2. La norma missionis come statuto costituzionale del Diritto canonico - 3. La communio come genus della corresponsabilità ecclesiale - 4. Trapianto da donatore non compatibile e problematiche di rigetto: non equiparabilità tra Diritto amministrativo canonico e statale - 5. Il concetto sui generis di Diritto amministrativo nella Chiesa cattolica - 6. Diversità strutturali nell’organigramma ecclesiale - 7. Il paradigma europeo come “analogatum princeps” del sistema canonico: verso un’amministrazione “di missione”.Specificity of canonical administrative law and “mission administration”. Ecclesial ministry as a requalification marker for  ontological-disciplinary autonomyABSTRACT: The need to configure a correct boundary within which to draw up the structure of administrative activity in the Church responds to the urgency to avoid undue and inaccurate transposition of concepts proper to secular juridical fields in the background of Canon law. In fact, in the Church it is not possible to speak of a "public administration-entity" but of an "administration-activity". It is not so much the subject that has to be examined, in view of a claim that is not suited to the foundational (top-down) and non-consociative (bottom-up) nature of the Church; as much as the concrete activities to be carried out within it, in the ideal of a shared responsibility that does not deprive the individual faithful of juridical positions that they can claim, but directs them within correct coordinates. The faithful do not live a dimension of "homo homini lupus", to reach an individual salvific finish line where one place to be conquered excludes that one of another. On the contrary, they pursue, united under the one baptism, the implementation of the mission of Christ, also through those juridical instruments which the Church has endowed through the story, but which are to be understood in their precise peculiarities, even though a relationship can not be excluded of mutual growth with secular law. According to this paradigm, the example of European Union law can be a valid benchmark for describing the particularities of ecclesial reality in a sector as specific as that of administrative law.
Keywords: Diritto ecclesiastico (Teoria generale del)